Analisis Efektivitas Penggunaan Bahasa Indonesia dalam Pelayanan dan Komunikasi di PMI Kota Gorontalo - Dali, Meilina Widya; Ramadani, Nurlatifa; Yunus, Siti Nur Aulia; Oktavialin, Zein; Humonggio, Paradiva Safarina; Potabuga, Della; Ntoma, Nazwa Safana Farahdiba; Habibie, Siti Nurhaliza; Selfi, Selfi; Kaluku, Nur Afriani S.; Mooduto, Tri Liyanda; Kamba, Moh. Raiyan Saputra; Pratiwi, Ike; Hasan, Shafyra; Rahmat, Salsabila (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
The Indonesian language holds a very vital position, not only as a national symbol but also as the main bridge in public service. This is particularly evident in the Indonesian Red Cross (PMI). As an organization directly involved in social and health sectors, PMI is required to communicate clearly so that the aid provided actually reaches and is understood by the public. Through an in-depth qualitative approach—through field observations, direct conversations (interviews), and document checks—it is evident that Indonesian indeed serves as the backbone of communication at PMI, both in direct conversations and written instructions. In general, its use has been quite effective. Even so, challenges still arise in the field. The issues that often occur usually revolve around the use of medical terms that are too technical for laypeople or inconsistent language style, which sometimes causes misunderstandings among the public. To minimize this, it seems important for PMI officers to regularly sharpen their communication skills through public service language training so that the humanitarian messages they convey can be received more warmly and clearly.